2017
DOI: 10.1039/c7md00424a
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic borneol derivatives as inhibitors of Marburg virus glycoprotein-mediated VSIV pseudotype entry

Abstract: Screening of a library of natural derivatives for their virus entry inhibition activity using pseudotype systems shows bornyl ester derivatives containing saturated N-heterocycles exhibiting the highest antiviral activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…1 H-and 13 C-NMR spectra were recorded on Bruker AV-300 ( 1 H: 300. 13 MHz, 13 C: 75.47 MHz), AV-400 Previously, we described the synthesis of several compounds according to the references 1, 2, 8, 9, 11, 13, 14, 16 -18, 20, 22 -25 [12] and 4 -7. [16] Synthesis of (1S,2R,4S)-1,7,7-Trimethylbicyclo…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 H-and 13 C-NMR spectra were recorded on Bruker AV-300 ( 1 H: 300. 13 MHz, 13 C: 75.47 MHz), AV-400 Previously, we described the synthesis of several compounds according to the references 1, 2, 8, 9, 11, 13, 14, 16 -18, 20, 22 -25 [12] and 4 -7. [16] Synthesis of (1S,2R,4S)-1,7,7-Trimethylbicyclo…”
Section: Methodsmentioning
confidence: 99%
“…[ ][ ] Of the borneol derivatives, N‐heterocyclic bornyl esters demonstrated high antiviral activity against influenza virus A/Puerto Rico/8/34 (H1N1) . Moreover, we have shown that some bornyl esters are able to specifically inhibit Marburg virus entry into the target cell . Thus, the 1,7,7‐trimethylbicyclo[2.2.1]heptane scaffold is an important pharmacophore for exhibiting high inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the introduction of pharmacophoric groups into camphor and fenchone molecules leads to formation of compounds showing antituberculous activity. Oxygen‐containing monoterpenes proved to be efficient against influenza virus and Marburg virus . Although the 1,2,3‐triazole moiety does not exist in nature, it has attracted interest as a candidate anticancer drug, particularly for the production of ‘1,2,3‐triazole‐natural compound’ hybrids .…”
Section: Introductionmentioning
confidence: 99%